2017
DOI: 10.1017/s1352465817000017
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary and Involuntary Imagery in Social Anxiety

Abstract: The phenomenology of negative imagery experienced by socially anxious individuals is idiosyncratic and may be inherently different from images generated for use in experimental research. Theoretical and clinical implications are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 34 publications
3
13
1
Order By: Relevance
“…Seventeen (56.67%) images were categorized into Theme 1 (negative self-images) while nine images (30.0%) were categorized into Theme 2 (negative images of other people). Images in Theme 1 were similar to the images reported in past studies as they included content such as experiencing anxiety symptoms and how they would look when they received negative reactions from others (Hackmann et al, 2000;Homer and Deeprose 2017). All except one image in Theme 1 were from an observer perspective, consistent with previous studies (Hackmann et al, 1998;Wells et al, 1998) and models (Clark and Wells, 1995;Rapee and Heimberg, 1997;Hofmann, 2007), which have stated that negative images are experienced mostly from an observer perspective.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Seventeen (56.67%) images were categorized into Theme 1 (negative self-images) while nine images (30.0%) were categorized into Theme 2 (negative images of other people). Images in Theme 1 were similar to the images reported in past studies as they included content such as experiencing anxiety symptoms and how they would look when they received negative reactions from others (Hackmann et al, 2000;Homer and Deeprose 2017). All except one image in Theme 1 were from an observer perspective, consistent with previous studies (Hackmann et al, 1998;Wells et al, 1998) and models (Clark and Wells, 1995;Rapee and Heimberg, 1997;Hofmann, 2007), which have stated that negative images are experienced mostly from an observer perspective.…”
Section: Discussionsupporting
confidence: 74%
“…Recent findings (Homer et al, 2016;Homer and Deeprose, 2017;Moscovitch et al, 2011) found that more images are experienced from the field perspective than previously thought. Homer and Deeprose (2017) suggested that the different focus of the imagethat is, anxiety centred on self versus anxiety centred on others, depending on the kind of idiosyncratic beliefs the individuals holdmay explain why these images are in the field perspective. Koreans tend to gauge others' thoughts, intentions and feelings to maintain harmony within the collectivistic culture (Kim et al, 2003).…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, previous studies demonstrating high frequencies of observer perspective imagery were conducted among individuals diagnosed with SAD (e.g. Hackmann et al, 1998Hackmann et al, , 2000Wells and Papageorgiou, 1999), whereas results in less symptomatic individuals show more modest rates of observer perspective (Moscovitch et al, 2011;Homer et al, 2016;Homer and Deeprose, 2017). Our results therefore suggest that the role of visual perspective in intrusive social imagery may be more nuanced than previously thought.…”
Section: Discussionmentioning
confidence: 41%
“…There is little research examining if these themes occur among individuals without SAD. Homer and Deeprose (2017) found that highly socially anxious undergraduate students reported experiencing intrusive images at least every 2 weeks, and commonly before social interactions. These participants also reported higher emotionality (shame, embarrassment) associated with intrusive images compared with deliberately generated images.…”
Section: Introductionmentioning
confidence: 97%
“…Hackmann, Clark & McManus, 2000;Homer & Deeprose, 2017) and causes anxiety, negative affect, decreased self-esteem, and poorer social performance (Hulme, Hirsch, & Stopa, 2012;Moscovitch et al, 2011;Hirsch, Clark, Mathews & Williams, 2003;Hirsch, Meynen & Clark, 2004; see Ng et al, 2014 for a review). In line with research showing that voluntary and involuntary memories can be independent (Conway and Pleydell-Pearce, 2000;Ehlers and Clark, 2000;Brewin and Holmes, 2003), intrusive social anxiety imagery is phenomenologically different to voluntarily generated imagery (for example, it may comprise self-representations or prospective imagery rather than contextualised episodic memories) and is associated with higher levels of anxiety (Homer & Deeprose, 2017). This study sought to extend the EMs paradigm to intrusive, involuntary imagery in a sub-clinical socially anxious sample, to yield stronger clinical implications than previous research using voluntarily-generated images in healthy samples.…”
Section: Introductionmentioning
confidence: 99%